Preschoolers´ Physical Activity and Time on Task During a Mastery Motivational Climate and Free Play - Wadsworth, Danielle D (2014)
The purpose of the present study was to determine the effect of a structured, mastery motivation physical education climate and an unstructured physical activity climate on time spent on task in a small sample of preschool children. Children enrolled in a public, federal-subsidized childcare center (N= 12) participated in two 45 minute physical activity programs within the school day. The structured climate consisted of a biweekly program of motor skill instruction that was based upon the key principles of a mastery motivational climate. The unstructured program was a daily 45 minute free play environment. Actigraph accelerometers monitored children’s participation in physical activity and time-on task was observed by a momentary time sampling technique. Results showed that time on-task significantly improved following a mastery motivational climate, and children spent 36% of their time in moderate-to-vigorous activity in this climate.  In contrast, time on-task did not significantly improve following participation in a free play environment and participants spent a majority of their time in sedentary behavior and accumulated no vigorous physical activity. Our results indicate that participation in physical activity impacts a preschooler’s ability to stay on task and the amount of physical activity accumulated during physical activity programming is dependent upon the climate delivered.